Mechanistic investigation on the microwave-assisted leaching of low-grade coal for low-ash coal production - Deb Barma, Santosh; Sathish, R; Rao, Danda Srinivas; Prakash, Ritesh (Separation science and technology, 2021)
The coal-derived energy can potentially be explored by utilizing the low-grade coals after beneficiation for power sector application on a long-term basis. However, beneficiating the low-grade coals of Indian origin to produce low-ash coal by physical or physicochemical techniques is very challenging due to their complex mineralogical nature. In this context, chemical beneficiation or leaching has proved to be an effective method. But, the high cost of chemicals associated with the leaching process limits its commercial practice. An in-depth investigation is, therefore, needed to optimize the chemical consumption so that the requirement of the chemicals can be minimized. Herein, a microwave-assisted leaching study was investigated on Indian low-grade coal to produce low-ash coal suitable for power generation. The raw coal and its flotation product were pretreated under optimized microwave pretreatment time (5 min) and subject to leaching at varying alkali concentrations. Among all the combinations, the leaching of microwave pretreated floated coal showed a higher degree of demineralization (69.57%) together with increased carbon content (55.48%) and gross calorific value (6635 kcal/kg) in its leached product. The leached products were also analyzed using different characterization techniques such as Fourier transform infrared spectrometer, X-ray diffraction, and Thermogravimetric analyzer.